Tubulointerstitial injury in proteinuric chronic kidney diseases - Cortinovis, Monica; Perico, Norberto; Remuzzi, Giuseppe (Frontiers in Medicine, 2024)
Proteinuria is an independent risk factor for chronic kidney disease progression and cardiovascular diseases. Apart from its prognostic role, the load of proteins that pass across the disrupted glomerular capillary wall trigger multiple pathophysiologic processes. These include, among others, intratubular complement activation and excessive proximal tubular reabsorption of filtered proteins, especially albumin and albumin-bound free fatty acids, which can set off several pathways of cellular damage. The activation of these pathways can cause apoptosis of proximal tubular cells and paracrine effects that incite the development of interstitial inflammation and fibrosis, ultimately leading to irreversible kidney injury. In this review, we provide a comprehensive overview of the current understanding on the mechanisms underlying the tubular toxicity of ultrafiltered proteins in the setting of proteinuric chronic kidney diseases. The acquired knowledge is expected to be instrumental for the development of novel therapeutic classes of medications to be tested on top of standard of care with optimized renin-angiotensin-aldosterone blockade and sodium-glucose cotransporter-2 inhibition, in order to further improve the clinical outcomes of patients with proteinuric chronic kidney diseases.